2009
DOI: 10.18632/aging.100016
|View full text |Cite
|
Sign up to set email alerts
|

Extension of chronological life span by reduced TOR signaling requires down-regulation of Sch9p and involves increased mitochondrial OXPHOS complex density

Abstract: The nutrient-sensing target of rapamycin (TOR) pathway appears to have a conserved role in regulating life span. This signaling network is complex, with many downstream physiological outputs, and thus the mechanisms underlying its age-related effects have not been elucidated fully. We demonstrated previously that reduced TOR signaling (intor1Δ strains) extends yeast chronological life span (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 38 publications
10
164
3
Order By: Relevance
“…4B), indicating that survival of Δmgm1 in stationary phase cells is severely compromised. Since it is known that survival of yeast in this phase depends on the ability to degrade cellular components by autophagy and on resistance to oxidative stress, among other factors, [33][34][35] it is tempting to speculate that the short-lived phenotype of the Δmgm1 mutant is due to ineffective mobilization of cellular resources or the result of the accumulation of oxidative damage to vital cellular components. Indeed, it was recently shown that energetically compromised mitochondria inhibit both induction of autophagy and the autophagic flux in baker's yeast.…”
Section: Resultsmentioning
confidence: 99%
“…4B), indicating that survival of Δmgm1 in stationary phase cells is severely compromised. Since it is known that survival of yeast in this phase depends on the ability to degrade cellular components by autophagy and on resistance to oxidative stress, among other factors, [33][34][35] it is tempting to speculate that the short-lived phenotype of the Δmgm1 mutant is due to ineffective mobilization of cellular resources or the result of the accumulation of oxidative damage to vital cellular components. Indeed, it was recently shown that energetically compromised mitochondria inhibit both induction of autophagy and the autophagic flux in baker's yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced TOR function leads to enhanced respiratory capacity in the absence of enhanced mitochondrial biogenesis, and this is required for chronological lifespan extension [50,95]. Instead of enhanced biogenesis, the result of reduced TOR signalling is more OXPHOS complexes per mitochondrion [96]. Moreover, ATP production is not elevated.…”
Section: Introductionmentioning
confidence: 99%
“…These findings lead the authors to speculate that these changes, which happen during cell proliferation and early cell cycle stages, precondition cells to a state promoting prolonged survival during the growth arrested period. Deletion of yeast S6 kinase (sch9), which also promotes enhanced chronological lifespan [97], is also linked to these changes in respiration [96,98]. Unlike chronological ageing, extension of yeast replicative lifespan by sch9D is not impaired by blocking accompanying enhancement of respiration [98].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the mTORC1 signaling pathway extends lifespan in various model animals, ranging from yeast (Kaeberlein et al, 2005a;Bonawitz et al, 2007;Pan and Shadel, 2009), C. elegans (Vellai et al, 2003), fly (Kapahi et al, 2004), to rodents (Harrison et al, 2009;Selman et al, 2009), thus establishing a close relationship between metabolism and aging. Studies from invertebrate models first demonstrated that inhibition of the mTOR signaling pathway is sufficient to reduce protein synthesis and increase lifespan (Vellai et al, 2003;Kapahi et al, 2004;Kaeberlein and Kennedy, 2008;Stanfel et al, 2009).…”
Section: Metabolic Signaling Pathways Insulin/igf Signaling In Metabomentioning
confidence: 99%